Judicial Control Over Economic Decisions - Al-Aliwi Al-Ziyadi, Ahmed Lafta Abd (Indonesian Journal Publisher, 2025)
Judicial oversight of economic decisions is one of the most important guarantees for improving the performance of economic decisions and is one of the most important principles and foundations that the state undertakes. The main purpose of this oversight is to advance the economic level, and the work is to shed light on the importance of economic decisions and to show that this topic has great importance and impact on the lives of citizens. Interest in the topic of economic decisions is interest in the lives of all people at the level of the Iraqi people. This research project is closely related to the present time, as it is based on finding solutions to some of the problems that people face in the economic situation. In this research, we relied on the inductive approach to legal and comparative texts. The study dealt with the general concepts of judicial oversight, and the study revealed the historical path of judicial oversight in Iraqi and Iranian law, and addressed the types, objectives and interests considered in economic decisions.